Digitalizing Malangan Mask Art for Cultural Preservation: An Elaboration Likelihood Model Study of Generation Z on Instagram and TikTok - Ni Made Savitri Paramita; Galih Edy Nur Widyaningsih (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2026)
The digital era demands new approaches to cultural preservation, including the safeguarding of intangible cultural heritage such as the Malangan mask dance of Malang Regency. This study examines how Generation Z engages with and processes digitalized Malangan mask content on social media, using the Elaboration Likelihood Model (ELM). Content was published on two dummy accounts (@topeng_ngalaman on Instagram and TikTok) and evaluated through a mixed-methods design combining a questionnaire of 22 Generation Z respondents with qualitative thematic analysis. Addressing the gap left by prior promotion-focused research, the study proposes a five-indicator content model content creativity, cultural narrative, audience engagement, information accessibility, and media optimization. The results show that content creativity and cultural narrative most strongly influenced engagement, yet most respondents followed the peripheral route, showing shallow elaboration of cultural–religious meaning. The findings indicate that digital preservation must move beyond visual appeal and algorithmic reach toward deliberate support for meaning-making and value transmission. As an exploratory pilot study with a small convenience sample (n = 22), the findings are indicative rather than generalizable.